VOCABULARY ENHANCEMENT USING CROSSWORD PUZZLE (WORD LINK) & GTM - Caroline Victorine Katemba (Universitas Islam Negeri Alauddin Makassar, 2022)
The English language is distinguished by its vocabulary. To master the four language-learning abilities of hearing, speaking, reading, and writing, vocabulary is essential. Many of the instructional strategies used to teach the English language are incorporated into vocabulary instruction, which achieves the same goals as earlier strategies. This study seeks to examine whether Word Link and Grammar Translation Method (GTM) will increase students' vocabularies. This research employs the Pre-experimental designs methodology. The pre-experimental group consisted of 25 fifth-graders from an Elementary School in West Bandung. A pre-test was administered at the beginning of the program, and a post-test was administered at the conclusion of the 32-hour meeting. The adoption of GTM utilizing the Word Link application (crossword puzzle) has a good and statistically significant impact on the vocabulary development of students, according to the findings of this study. The crossword puzzleword Link apps appear to aid youngsters in expanding their vocabularies, and it is recommended that teachers employ this strategy while teaching and studying English, particularly in the early grades.in elementary school.